Bergman Island [videorecording (DVD)] - Hansen-Løve, Mia, 1981-; Krieps, Vicky, 1983-; Roth, Tim; Wasikowska, Mia, 1989-; Danielsen Lie, Anders, 1979- (Criterion collection, 2023)
In search of inspiration for their current filmmaking projects, Chris and her partner travel to the remote island of Fårö, Sweden, where Bergman lived and worked for decades. There, the spirit of the cinema master looms as Chris confronts her complicated relationships with work, men, motherhood, and her artistic influences.